ANALISIS PERUBAHAN PENGGUNAAN LAHAN DI WILAYAH PESISIR KOTA PEKALONGAN MENGGUNAKAN DATA LANDSAT 7 ETM+ - Shofiana, Rina; Subardjo, Petrus; Pratikto, Ibnu (977-2407769)
The research of land use change is very important for this time, because of changes in land use have an impact on the physical and social environment. The purpose of this research is to determine the extent and causes of land use change in Pekalongan coastal area from 1999 - 2012 using the data of Landsat 7 ETM+ satellite image. This research uses unsupervissed classification method by using the Er Mapper 7.0 software. Then to analyze the land use change using overlay land use maps of 1999, 2006, and 2012 use ArcGIS 9.3 software. The results showed that the land use change in the Pekalongan coastal from 1999 - 2012 shows pool is the largest additional land use changes the amount of Â± 334.91 ha. This caused by rob in the research area. While vacant land is the largest land use which have a reduction in the amount of Â± 792.86 ha. It is influenced by human factors such as population growth (number and distribution), the increase was also influenced by economic and physical factors such as topography, and soil type. Based on the results of the land use change research in the Pekalongan coastal from 1999 - 2012 there are some additional and reduction.